CENTRAL DETERMINER IN ABSTRACTS JOURNAL - Winantu Kurnianingtyas Sri Agung; Aries Fitriani (Al-Lisan: Jurnal Bahasa, 2019)
Central determiner is as the main component in constructing noun phrase element as subject, objects, and complement in writing compositions. Meanwhile, determiner affects the meaning of noun. This research investigates the constructions of central determiners in abstracts of Journal Al-Tahrir Volume 17 No.1 Tahun 2017 and the reasons in applying those determiners in that journal. In gaining related information, types of central determiners, three diagram and table bracket were used. Qualitative research and syntactical analysis was conducted to analyze the data. The research finding revealed that central determiners were used in sentences of the abstracts. The terms of central determiners in subject were constructed through 7 determiners such demonstrative article, personal pronoun, possessive pronoun, indefinite pronoun, demonstrative article, definite article, and indefinite article. Having the function of object, central determiners were defined in 5 terms namely possessive pronoun, indefinite pronoun, demonstrative article, definite and indefinite article. Then, they were also used in sentences of the abstracts as complement. Here, central determiners were defined in terms of reflective pronoun, personal pronoun, possessive pronoun, indefinite pronoun, interrogative pronoun, definite and indefinite article.